Analisis Kesiapan Otoritas Pajak dalam Pemajakan atas Ekonomi Digital - Firmansah, Bambang; Rahayu, Ning (JPSI (Journal of Public Sector Innovations), 2020)
The patterns, forms of human behavior and the presence of many new forms of business today such as e-commerce, payment services, application services, online advertising, cloud computing, high frequency trading, participative networked platforms are influenced by the digital revolution as formulated by the OECD. Social phenomena as an effect of the rapid development of information and communication technology (ICT) known as the digital economy will certainly also change the patterns of business individuals and organizations throughout the world. With the presence of various new business models, there are many opportunities for tax avoidance schemes that are usually dominated by multinational entities (MNE). Based on this, the OECD recommends several action plans, one of which is about the digital economy. The need to detect the digital economy by the tax authorities of world countries such as Indonesia is now very large. Related to this the Indonesian government issued a unilateral regulation namely Perpu Number 1 of 2020 which later became Law No. 2 of 2020, one of which regulates taxation of the digital economy. The Indonesian tax authority seeks to respond to the dynamics of the internal and external environment called organizational readiness. This study wants to analyze whether the Indonesian tax authority is ready to tax the digital economy.